Stroop Test among patients suffering from depressive disorders and schizophrenia - Talarowska, Monika; Florkowski, Antoni; Orzechowska, Agata; Mossakowska-Wójcik, Joanna; Gałecki, Piotr (Current Problems of Psychiatry, 2011)
Aim: The aim of the study isthe evaluation of verbal-auditory working memory and executive functions efficacy in patients with depressive disorders and patients with schizophrenia. Cognitive functions were evaluated by the Stroop Color Word Interference Test (Stroop test). Method: A sample of 104 persons aged 18-55 years (M = 43.66; SD ± 13.27) participated in the study. Study participants were divided into two groups: patients with schizophrenia (n=44) and patients with depressive disorders (n=60). The mean results in Positive and Negative Syndrome Scale (PANSS) for schizophrenia patients: M = 68.67; SD ± 28.83. The mean results in Hamilton Depression Rating Scale (HDRS) for patients suffering from depressive disorders: M = 21.08; SD ± 5.93. Results: Any relevant statistical differences among examined group were not observed. The worse results in the first part of Stroop Test (RCNb) achieved depressive patients: time (s) - M = 34.28; SD ± 15.94 (patients with schizophrenia: M = 29.79; SD ± 11.81). In the second part of Stroop Test (NCWd) the worse results obtained schizophrenic patients: time (s) - M = 90,39, SD = 46,03, number of errors - M = 4.43; SD ± 7.44 (depressive patients: time (s) M = 79.77; SD ± 49.41, number of errors – M = 3.29; SD ± 5.58. Conclusions: 1. Depressive patients do not differ from schizophrenic patients in Stroop test performance.